A ctenochasmatid pterosaur from the Portland Limestone Formation (Late Jurassic, Tithonian) of southern England - Smith, Roy E.; Martill, David M. (Proceedings of the Geologists' Association, 2025)
A new specimen of pterosaurian mandible from the Late Jurassic (Tithonian) Portland Limestone Group of southern England is described. Morphological considerations permit assignment to Pterodactyloidea. The elongate slender mandible and numerous closely spaced alveoli suggest it is a member of the Ctenochasmatidae. A faint median ridge on the occlusal surface between two grooves, converging into a median groove anteriorly, and the lack of a distinct premaxilla suggest the specimen is part of the symphysis of the mandible. This is the first documented record of a pterodactyloid from the Portland Group of England.